Perancangan dan Implementasi Pangkalan Data Sekolah Menengah Atas dan Kejuruan di Kabupaten Nabire Berbasis Web - Ester Ayuk Pusvita; Nayla Jenifer (Jurnal Teknologi dan Informatika, 2025)
The purpose of this research, "Designing a Database System for Senior High Schools/Vocational Schools in Nabire Regency," is to build an information system that will make the process of data processing and management for schools in Nabire Regency easier. In this era of rapid technological advancement, effective and open information systems are becoming increasingly important, especially for educational purposes. It is hoped that the Ministry of National Education (Kemendiknas) will develop an information system with school profile data across Indonesia. This will assist data-driven decision-making for various parties, including the government and the education department. With this system, it is hoped that the administrative process will become more effective and transparent, and policy-making will become easier. In addition, this research emphasizes the importance of ensuring that all stakeholders can access data in order to improve the quality of education in the area. This study shows that the application created not only makes data management easier, but also enhances clarity and integrity in public education services. Therefore, it is hoped that this system will become a useful tool to promote education and assist in better decision-making processes in Nabire Regency. This research significantly contributes to the development of educational information systems in Indonesia, particularly in terms of school data management.